2004
DOI: 10.4321/s1130-01082004000600008
|View full text |Cite
|
Sign up to set email alerts
|

Pyoderma gangrenosum associated with ulcerative colitis: response to infliximab

Abstract: Pyoderma gangrenosum is an extraintestinal manifestation of inflammatory bowel disease that can be therapeutically troublesome. We comment on the case of a patient with clinically inactive ulcerative colitis who progressively developed necrotic lesions on both tibial aspects of his legs, which corresponded both clinically and histologically to pyoderma gangrenosum. Treatment with steroids and azathioprine could not control this complication. A single dose of infliximab 5 mg/kg was given, achieving an impressiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] The vast majority of these reports describe patients with PG who were treated with infliximab for underlying CrohnÕs disease. The largest series of PG patients treated with infliximab is a multicenter retrospective study by Regueiro et al 20 In this study, 13 patients with long-standing inflammatory bowel disease (12 with CrohnÕs disease, 1 with ulcerative colitis) and refractory PG were treated with infliximab.…”
Section: Infliximabmentioning
confidence: 99%
See 1 more Smart Citation
“…[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] The vast majority of these reports describe patients with PG who were treated with infliximab for underlying CrohnÕs disease. The largest series of PG patients treated with infliximab is a multicenter retrospective study by Regueiro et al 20 In this study, 13 patients with long-standing inflammatory bowel disease (12 with CrohnÕs disease, 1 with ulcerative colitis) and refractory PG were treated with infliximab.…”
Section: Infliximabmentioning
confidence: 99%
“…[22][23][24][25][26][27][28][29] Most recently, the use of infliximab in the treatment of chronic lymphocytic leukemia-associated PG has been reported. 36 Importantly, this patient did not have inflammatory bowel disease.…”
Section: Infliximabmentioning
confidence: 99%
“…In the most severe and corticorefractary cases, cyclosporine A, tacrolimus, azathioprine, or micophenolate mofetil, ciclophosphamide, clorambucil, intravenous gammaglobulin, thalidomide, etanercept, Infliximab, adalimumab, clofazimine, dapsone, metronidazole and nicotine have been used (14)(15)(16)(17)(18). Some studies have shown that treatment of resistant cases can be done with other immunosuppressants.…”
Section: Discussionmentioning
confidence: 99%
“…The relation between between PG and the extension, length and severity of IBD is controversial. PG is a relatively rare extraintestinal presentation of ulcerative proctocolitis, and its incidence ranges from 2 and 12% 17,18,19 , affecting both genders and all age groups. It is also associated with Chron's disease, however, the prevalence of such association is lower than the one observed for ulcerative proctocolitis 20,21 .…”
Section: Discussionmentioning
confidence: 99%